Detection of Arc/Arg3.1 oligomers in rat brain: constitutive and synaptic activity-evoked dimer expression in vivo - Mergiya, Tadiwos F.; Gundersen, Jens Edvard Trygstad; Kanhema, Tambudzai; Brighter, Grant; Ishizuka, Yuta; Bramham, Clive R. (Frontiers in Molecular Neuroscience, 2023)
The immediate early gene product activity-regulated cytoskeleton-associated protein (Arc or Arg3.1) is a major regulator of long-term synaptic plasticity with critical roles in postnatal cortical development and memory formation. However, the molecular basis of Arc function is undefined. Arc is a hub protein with interaction partners in the postsynaptic neuronal compartment and nucleus. Previous in vitro biochemical and biophysical analysis of purified recombinant Arc showed formation of low-order oligomers and larger particles including retrovirus-like capsids. Here, we provide evidence for naturally occurring Arc oligomers in the mammalian brain. Using in situ protein crosslinking to trap weak Arc–Arc interactions, we identified in various preparations a prominent Arc immunoreactive band on SDS-PAGE of molecular mass corresponding to a dimer. While putative trimers, tetramers and heavier Arc species were detected, they were of lower abundance. Stimulus-evoked induction of Arc expression and dimer formation was first demonstrated in SH-SY5Y neuroblastoma cells treated with the muscarinic cholinergic agonist, carbachol, and in primary cortical neuronal cultures treated with brain-derived neurotrophic factor (BDNF). In the dentate gyrus (DG) of adult anesthetized rats, induction of long-term potentiation (LTP) by high-frequency stimulation (HFS) of medial perforant synapses or by brief intrahippocampal infusion of BDNF led to a massive increase in Arc dimer expression. Arc immunoprecipitation of crosslinked DG tissue showed enhanced dimer expression during 4 h of LTP maintenance. Mass spectrometric proteomic analysis of immunoprecipitated, gel-excised bands corroborated detection of Arc dimer. Furthermore, Arc dimer was constitutively expressed in naïve cortical, hippocampal and DG tissue, with the lowest levels in the DG. Taken together the results implicate Arc dimer as the predominant low-oligomeric form in mammalian brain, exhibiting regional differences in its constitutive expression and enhanced synaptic activity-evoked expression in LTP.